Ethical problems in pediatric cardiology - T, Jurko; A, Jurko; M, Mešťaník; M, Minarik; M, Zibolen (Journal of Cardiovascular Medicine and Cardiology, 2022)
The authors discuss new ethical problems associated with the use of modern diagnostic and therapeutic modalities in pediatric cardiology. They underline the role of pediatric cardiologists in the process of approaching specific ethical problems. In the assessment of specific medical problems, authors pay greater attention to ethical principles of beneficence and nonmaleficence, which continue to be problematic areas in pediatric cardiology.